Association of Low Cardiac Output Syndrome with in Hospital Outcomes after on Pump Coronary Artery Bypass Grafting Surgery - Ajwad Farogh, Ahmad Hasan, Farah Naz, Jacollin George, Shagufta Emmanuel, Ayyazda Farhana, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The main objective of current study was to explore the frequency of Low Cardiac Output Syndrome (LCOS) in patients underwent on-pump CABG. Study design and place: The study was carried out in Cardiac Care Center, Bahawalpur From March 15, 2019, to October 31, 2020, Materials and Methods: This prospective, descriptive study was conducted in the Cardiac Surgery, Cardiac Center Bahawalpur, Punjab. Total 250 patients were enrolled in this prospective, comparative study and divided into two groups. Group A (LVEF ≥40% ) and Group B LVEF <40%) the frequency of LCOS postoperatively was compared. the study was conducted. This study employed the non-probability, purposive sampling method. SPSS 22 was used to analyze data. Significant data was used as P-value 0.05. Results: The average age of the participants was 50 ± 4.67 in Group A as compare with Group B (53.44 ± 3.24) years with p-value 0.034. Total 144(57.6%) Male and 106(42.4%) were female patients. The frequency of LCOS was 19(15.2%) versus 25(20%) (P=0.021). Findings showed that the significant difference in outcomes in terms of Renal Dysfunction, Prior CVA, Stroke, ICU stay(days), Recent MI and mortality between the groups without LCOS and with LCOS. The findings of current study can be helpful for management in patients with low Ejection Fraction undergoing CABG which has been shown a higher perioperative risk and a better survival after myocardial revascularization. In this setting the long-term benefits clearly overcome an increased peri-operative mortality Conclusion: Those with pre-operative LVEF less than 40% had a significantly different frequency of LCOS than patients with LVEF greater than 40%. In comparison to patients without LCOS, individuals with LCOS had considerably worse outcomes in terms of stroke, respiratory failure, renal failure, ICU stay, hospital stay, and death. Keywords: CABG, LCOS, LVEF, CVA, MI, ICU